2022
DOI: 10.3390/ijerph19084755
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and Expectations of Ethnic Minorities and Majorities towards Community Pharmacy Medicines-Related Services in Estonia

Abstract: The unique professional competence of pharmacists can support the safe and effective use of medicines by patients. Additionally, it is important to acknowledge and incorporate the needs of patients with various cultural and social backgrounds. The objective of this study was to assess and compare the experiences and expectations of Russian- and Estonian-speaking pharmacy customers about medicines-related services in Estonian community pharmacies. Cross-sectional study among pharmacy customers was conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Other studies have also observed a high appreciation for pharmacy services among ethnic minorities 35,36 . A UK study showed that ethnic minority members appreciated the supportive role of community pharmacists and how these break down barriers to health service access, increase health awareness and build trusting relationships 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also observed a high appreciation for pharmacy services among ethnic minorities 35,36 . A UK study showed that ethnic minority members appreciated the supportive role of community pharmacists and how these break down barriers to health service access, increase health awareness and build trusting relationships 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also observed a high appreciation for pharmacy services among ethnic minorities. 35 , 36 A UK study showed that ethnic minority members appreciated the supportive role of community pharmacists and how these break down barriers to health service access, increase health awareness and build trusting relationships. 37 Community pharmacists have also been reported as the most accessible primary care HCPs, and the advantages they provide include medicines consultations, quick access without booking appointments, and convenient timing.…”
Section: Discussionmentioning
confidence: 99%